Pyrrolidine Dithiocarbamate Prevents Neuroinflammation and Cognitive Dysfunction after Endotoxemia in Rats - Kan, Min Hui; Yang, Ting; Fu, Hui Qun; Fan, Long; Wu, Yan; Terrando, Niccolò; Wang, Tian-Long (Frontiers in Aging Neuroscience, 2016)
Systemic inflammation, for example as a result of infection, often contributes to long-term complications. Neuroinflammation and cognitive decline are key hallmarks of several neurological conditions, including advance age. The contribution of systemic inflammation to the central nervous system (CNS) remains not fully understood. Using a model of peripheral endotoxemia with lipopolysaccharide (LPS) we investigated the role of NF-κB activity in mediating long-term neuroinflammation and cognitive dysfunction in aged rats. Herein we describe the anti-inflammatory and neuropretective effects of pyrrolidine dithiocarbamate (PDTC), a selective NF-κB inhibitor, in modulating systemic cytokines including tumor necrosis factor-α and interleukin-1β (IL-1β) and CNS markers after LPS exposure in aged rats. In the hippocampus, PDTC not only reduced neuroinflammation by modulating canonical NF-κB activity but also affected IL-1β expression in astrocytes. Parallel effects were observed on behavior and PSD95, a marker of synaptic function. Taken together these changes improved acute and long-term cognitive function in aged rats after LPS exposure.